Homocysteine Levels and Lipid Peroxidation in Cases With Toxic Multinudular Goitre - Çıkım, Gürkan; Ozan, Gonca; Gülcü, Funda; Baykan, Davut; Gürsu, M.ferit (Fırat University, 2004)
Objective: Toxic multinodular goitre (TMG) is known to be a frequent endocrine pathology. Increased thyroid hormones cause excess oxygen consumption; therefore, free radical generation increases. Consequently, oxidative stress, which has been implicated in several disorders, develops. Recently, homocysteine also was shown as a prooxidant. The aim of the present study was to compare first diagnosis, pre-operative and postoperative levels of MDA, homocysteine and thyroid hormones and to investigate the benefits of these parameters in diagnosis. Material and Method: Present study was carried out on 24 female patients diagnosed with toxic multinodular goitre; and they were divided into three groups as first diagnosis (TMG), medical treated (pre-operative; TMG-Pr) and post-operative (TMG-Po). Thyroid hormones of patients were determined with IMMULITE 2000 hormone auto-analyzer; homocysteine levels were determined by using Elx-800 system and MDA levels were determined with the manual spectrophotometric method of Satoh. Results: Homocysteine levels of TMG, TMG-Pr and TMG-Po were determined as 8.1±1.9; 10.1±1.8 and 10.5±2.6 µmol/L, respectively. The levels of MDA were determined; there was an increase in TMG group (1.9±0.4 nmol/ml) and a decrease in TMG-Pr (1.0±0.8 nmol/ml) and TMG-Po (1.1±0.7 nmol/ml) groups. These two parameters were changed significantly in both TMG-Pr and TMG-Po groups, compared with TMG group (p

Amaç: Toksik multinodüler guatr (TMG) oldukça sık görülen endokrin bir patolojidir. Tiroid hormonlarındaki artış mitokondrial serbest radikal oluşumu artırmaktadır. Oksidatif stres birçok hastalığın oluşum ve gelişiminden sorumlu tutulmaktadır. Son yıllarda homosistein de prooksidan bir madde olarak gösterilmektedir. Bu çalışmanın amacı ilk tanıda, preoperatif ve cerrahi tedavi sonrası serum malondialdehit (MDA), homosistein ve tiroid hormon düzeylerini karşılaştırmak ayrıca tanıda bu parametrelerin önemini araştırmaktır. Gereç ve Yöntem: Çalışma toksik multinodüler guatr tanısı almış 24 kadın hastada yapıldı ve hastalar ilk tanı alan (TMG), medikal tedavi sonrası (preoperatif; TMG-Pr) ve operasyon sonrası (postoperatif, TMG-Po) olmak üzere 3 gruba ayrıldılar. Hastaların tiroid hormonları İMMULITE 2000 marka hormon oto analizöründe, homosistein düzeyleri ELX-800 cihazında; MDA düzeyleri ise Satoh'dan alınan manuel spektrofotometrik yönteme göre belirlenmiştir. Bulgular: TMG, TMG-Pr ve TMG-Po'da homosistein düzeyleri sırası ile 8.1±1.9; 10.1±1.8 ve 10.5±2.6 µmol/L, olarak tespit edilmiştir. TMG'li hastalarda, MDA düzeyleri artmış (1.9±0.4 nmol/ml), TMG-Pr (1.0±0.8 nmol/ml) ve TMG-Po'da (1.1±0.7 nmol/ml) ise azalma olduğu tespit edilmiştir. Her iki parametre preoperatif ve postoperatif gruplarda tedavi öncesine göre olarak anlamlı şekilde değişmektedir (p
Toksik Multinodüler Guatrlı Olgularda Homosistein Düzeyi ve Lipid Peroksidasyonu